ANALISIS KETIMPANGAN DISTRIBUSI PENDAPATAN NELAYAN DI DESA BUHIAS KECAMATAN SIAU TIMUR SELATAN KABUPATEN KEPULAUAN SIAU TAGULANDANG BIARO - Ronald N. Pakasi; Charles R. Ngangi; Rine Kaunang (Universitas Sam Ratulangi, 2015)
ABSTRACT This study aims to analyze the income of fishermen in the village Buhias well as the extent of inequality of income distribution fisherman research area. This study uses primary data in the form of data obtained from the distribution of questionnaires. Sampling method performed by the method of proportional allocation ( Proportional Allocation Method) . The analytical method used is the analysis of income, an indicator of the level of inequality based on the Gini Ratio fitted with Lorenz curve and the World Bank criteria . The results showed that the income of fishermen in the village sample Buhias bervareasi enough and tend to be different . The level of income inequality based on the Gini Ratio fishermen for 0.531 were in the high category , while according to the World Bank are in the medium category . Keywords : Fisherman , Income , Gini Ratio , Lorenz curve , and World BankÂ